Bifurcation results for a Kirchhoff type problem involving sign-changing weight functions. (June 2020) - Xu, Xian; Qin, Baoxia; Chen, Siyu
Abstract: In this paper we establish some existence results for both compact and unbounded connected components of the positive solutions set of a nonlocal problem of the Kirchhoff type. The methods to show our main results are the local and global bifurcation techniques, a priori bounds for elliptic equation, and the properties of the principal eigenvalues. To obtain the a priori bounds for Kirchhoff type elliptic equation, some new techniques are introduced.